Investigation of Supramolecular Nanofibers Formed from Multicomponent Nucleotide‐Appended Bolaamphiphiles and Heteropolymeric DNA as a Template. Issue 11 (15th September 2016) - Iwaura, Rika; Kanai, Yoshikazu; Ohnishi‐Kameyama, Mayumi
Abstract: A novel DNA‐templated multicomponent self‐assembly of well‐defined, molecular‐level‐controlled nanostructures in aqueous solution is demonstrated by using a thermal cycling procedure. The strategy uses four building blocks comprising 1, 18‐nucleotide‐appended bolaamphiphiles (3′‐phosphorylated adenosine, thymidine, guanosine, or cytidine connected to each end of an oligomethylene chain) and a heteropolymeric 58‐mer containing a palindromic sequence as the template DNA. Atomic force microscopic observations, circular dichroism, and temperature‐dependent absorption spectra revealed that the multicomponent self‐assembly of the four nucleotide bolaamphiphiles and template DNA formed right‐handed helical nanofibers with complementary base pairs during thermal cycling. Nanofibers were not formed if one of the four nucleotide bolaamphiphiles was missing, suggesting that construction of the helical nanofiber resulted from self‐assembly of all four bolaamphiphiles to form matched base pairs sorted according to the sequence of the template DNA. Abstract : Sorting through your letters : The construction of helical nanofibers by the self‐assembly of four types of nucleotide‐appended building block molecules has been reported. These nucleotides formed matched base pairs that were sorted according to the base sequence of the template DNA (see figure).